Comparison of Emotional Schemes in War Veterans suffering Post Traumatic Stress Disorder with Depression Symptoms, Anxiety Symptoms and without Signs of Depression and Anxiety - M.M Zare; H. Bagooli; S.A. Kazemi; H.A. Javidi (Afarand Scholarly Publishing Institute, 2020)
Aims: War veterans suffering post-traumatic stress disorder (PTSD) have difficulty with emotional regulation strategies. The model of emotional schemas as a transdiagnostic construct recently played a major role in researches related to mental illnesses. The aim of this study was to compare the emotional schemes in war veterans suffering post-traumatic stress disorder with depression symptoms, anxiety symptoms and without signs of depression and anxiety. Instruments & Methods: In this descriptive study 105 war veterans suffering post-traumatic stress disorder who referred to counseling centers of Martyr and Sacrifices Affairs Foundation of Shiraz and Bavanat cities, were selected by purposive sampling method and divided into three groups of 35 people of war veterans suffering PTSD with depression symptoms, war veterans suffering PTSD with anxiety symptoms, and war veterans suffering PTSD without symptoms of anxiety and depression. Tools of the study were Structured Clinical Interview (SCID-5), Beck Depression Inventory, Beck Anxiety Inventory, Iranian version of Leahychr('39')s Emotional Schema Questionnaire, and military version of the PTSD Checklist (PCL). Data were analyzed by SPSS 22 software using univariate analysis of variance and LSD post hoc test. Findings: There was significant difference among the three groups of veterans in all aspects of emotional schemas except subjective rumination, consensus and higher values (p<0.05). Conclusion: Emotional schemas are different in war veterans suffering post-traumatic stress disorder with depression symptoms, anxiety symptoms and without signs of depression and anxiety, so in treatment of these patients the role and the replacement of compatible emotional schemes in recovery of the disease should be considered.